1988
DOI: 10.1557/jmr.1988.0729
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial phenomena involving liquid metals and solid oxides in the Mg–Al–O system

Abstract: The wetting of ceramic surfaces by aluminum alloys has been reexamined using a chemical system where interfacial reactions and oxide film effects could be isolated. The system Al–Mg–O was chosen since it is technologically important and high-purity, well-characterized materials are readily available. Magnesium alloyed with the aluminum sessile drop and silicon picked up from the experimental apparatus cause an initial reduction in contact angle by altering the protective nature of the oxide film formed on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 23 publications
2
28
1
Order By: Relevance
“…Observation of the inside of the cavity shows micro-channels which can act as an easy path allowing the diffusion of Mg, which reacts with the oxygen to develop the nodular structure (MgO). 20) Oxidation persists and the nodular structure coarsening causes the microchannels to gradually fill up the interface between the magnesium matrix and the oxide film. In the AM50A alloy, the fractured surface shows a granular fracture mode.…”
Section: Fracturing Mode Of the Eroded Oxide Filmmentioning
confidence: 99%
“…Observation of the inside of the cavity shows micro-channels which can act as an easy path allowing the diffusion of Mg, which reacts with the oxygen to develop the nodular structure (MgO). 20) Oxidation persists and the nodular structure coarsening causes the microchannels to gradually fill up the interface between the magnesium matrix and the oxide film. In the AM50A alloy, the fractured surface shows a granular fracture mode.…”
Section: Fracturing Mode Of the Eroded Oxide Filmmentioning
confidence: 99%
“…It has been reported in preparing aluminum matrix composites that the reactions among aluminum, magnesium and SiO 2 results in the formation of MgAl 2 O 4 and MgO. [10][11][12] A peak of silicon was also detected in each profile. This indicates that the silicon which remains in the reaction product (Fig.…”
Section: Methodsmentioning
confidence: 80%
“…It is reported by MacZura [45][46] that tabular alumina T-61 grade with <0.01% Na2Û is produced from 0.4-0.5% Na2Û containing calcined alumina feedstock. However, excess usage of boric acid causes channelling problems at the cooler portion of the shaft furnace because of condensation of sodium boride compounds.…”
Section: Tabular Aluminamentioning
confidence: 99%
“…Weirauch [45] reported that no reaction product observed using both optical and scanning electron microscopy methods at Al-3 wt%Mg / saffhire interface after 24 hours of contact time at 800°C. However, experiments conducted using Al-6 wt%Mg alloy by keeping the other experimental conditions constant, a mixture of spinel and (X-AI2O3 was found at the interface.…”
Section: * Mamentioning
confidence: 99%